Continuous renal replacement therapy (CRRT) in children - Bunchman, Timothy E. (Henry Stewart Talks, 2021)
Convection clearance vs. diffusive clearance in CRRT, Vascular access in CRRT, Drug clearance, Solutions used in CRRT, Indications for CRRT (AKI, intoxications, in born error of metabolism), Timing of CRRT initiation